Nigerian Female with Skin Lesions in the Leg and Face: Herpetic Sycosis Folliculitis - Dominique Dilorenzo; Naganna Channaveeraiah; Patricia Gilford; Bruce Deschere (Case Reports in Infectious Diseases)
Nongenital HSV 1 presents outside the mucus membrane. Our patient had unusual presentation that caused diagnostic dilemma. 30-year-old native Nigerian female coming with fiancée to the United States presented to our service one day after arrival through ER with a lesion on her right ankle. She was diagnosed with cellulitis, started on antibiotics, and admitted to hospital. She had fever of 39.1°C. Head and neck exam showed multiple sized lesions over tongue and palate and inner aspect of lower lip. Abdomen and genital exam was normal. Skin exam showed lesions over the face and lesions over the lateral aspect of the right leg. There was ulcerated lesion over the right lateral malleolus with surrounding erythema and edema. Her tests showed elevated ESR of 98; HIV test was negative; CT scan of the ankle showed no abscess or osteomyelitis. TB quantiferon was indeterminate; AFB stain and culture were negative; HSV IgM was elevated at 1 : 16; RPR was negative; ANA was negative; malaria screen was negative, and blood cultures were negative for bacteria, fungus, and virus. Debrided wound had no growth of bacteria or fungus or virus. This case illustrates the unusual presentation of the HSV1 outside the mucus membrane and how it can be confused with other conditions that required extensive tests. Therapeutic trail with antiviral medications resolved lesions over the leg and face.